2011
DOI: 10.1002/stem.668
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: A Bioassay to Identify Primary Human Prostate Cancer Repopulating Cells

Abstract: Cancer cells are heterogeneous in both their phenotypes and ability to promote tumor growth and spread. Xenografting is used to identify the most highly capable cells of regenerating tumors, referred to as cancer repopulating cells. Because prostate cancers (PCa's) rarely grow as xenografts, indentifying PCa repopulating cells has not been possible. Here, we report improved methods to xenograft localized primary PCa tissues using chimeric grafts with neonatal mouse mesenchyme. Xenograft survival of tumor tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 16 publications
0
57
2
Order By: Relevance
“…Grafts were implanted under the kidney capsule of NOD/SCID g (NSG) mice and analysed using immunohistochemistry (Table 1). This technique has been used extensively and has been described by this group [17][18][19]. Uropathologists (D.C. and J.P.)…”
Section: Methodsmentioning
confidence: 99%
“…Grafts were implanted under the kidney capsule of NOD/SCID g (NSG) mice and analysed using immunohistochemistry (Table 1). This technique has been used extensively and has been described by this group [17][18][19]. Uropathologists (D.C. and J.P.)…”
Section: Methodsmentioning
confidence: 99%
“…For example, data from Loda and coworkers suggested that if survival is specifically considered as the presence of malignant foci in grafts at the time of harvest, and not merely the ability to retrieve graft tissue, then overall survival rates are actually significantly lower than first reported [31]. We, and others, specifically reported the survival of malignant foci, rather than survival of human tissue regardless of the pathology detected, to be ∼50% [31,34]. This could be due to the loss of malignant foci in the graft in the host milieu, through mechanisms such as apoptosis, or failure to survive or grow in the first place.…”
Section: Primary Tissuesmentioning
confidence: 75%
“…Soft agar cloning experiments are typically used to detect the growth of non-adherent of tumor cells (Bentivegna et al, 2010;Toivanen et al, 2011). Not all tumor cells have the ability to form colonies in soft agar; colony formation of tumor cells is positively correlated with their tumorigenic ability (Freedman et al, 1974).…”
Section: Discussionmentioning
confidence: 99%